The Effect of Human Resource Competency and Organizational Culture on Employee Performance through Work Motivation as an Intervening Variable (Study on State Apparatus in the Attorney General's Office) - Puspitasari, Yunita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The aims of the study were: 1) To determine the effect of competence and organizational culture on employee motivation in the state apparatus within the Attorney General's Office. 2) To analyze the influence of competence, organizational culture, and motivation on state civil servant performance within the Attorney General's office of the Republic of Indonesia. 3) To analyze the effect of competence on employee performance through work motivation as a mediator for state civil apparatus employees in the Attorney General's Office. 4) To analyze the influence of organizational culture on employee performance through work motivation as a mediator for employees of the state civil apparatus in the Attorney General's Office. This study uses a quantitative research method with data collection techniques from 60 respondents who are state civil servants at the Bureau of Planning and Equipment Bureau within the Office of the Attorney General's Office. The analytical method used in this study uses descriptive analysis and path analysis. The results of this study state that: 1) competence and organizational culture positively influence the motivation of ASN work in the Attorney General's Office. 2) There is a positive influence of competence, organizational culture, and motivation on the performance of civil servants in the Attorney General's Office. 3) There is a positive influence of competence on the performance of civil servants in the Attorney General's Office through motivation as an intervening variable. 4) Organizational culture positively influences the performance of civil servants in the Attorney General's Office through motivation as an intervening variable.